Role of post-operative carcinoembryonic antigen as predictor of outcome: Evaluation of patients with colorectal malignancy at a tertiary care center - Sanjay Devidas Dakhore; Shilpa Namdev Pande; Suraj Govind Jadhao; Nilesh Parashuram Mangam; Dnyanesh Balkrishna Amle (Asian Journal of Medical Sciences, 2022)
Background: Colorectal cancer is the third most common cancer worldwide. The colorectal cancer has varied presentation and often patients present in late stages of disease. Pre-operative carcinoembryonic antigen (CEA) levels are indicative of tumor stage and thus are predictive of prognosis. However, the importance of post-operative CEA value is seldom discussed and utility of this clinically relevant parameter needs to be established to predict survival of subjects after surgical resection of tumor. Aims and Objectives: This study aims to understand the colorectal malignancy in a group of population and evaluate its complexity, clinical presentations, modalities of treatment, and its complications. Furthermore, we aimed to access predictive utility of post-operative CEA levels for forecasting the long-term outcome in the patient. Materials and Methods: All subjects with diagnosed cases of colorectal malignancy were included in the study. The subjects presenting complaints were clinically examined and the observations were noted. Colonoscopy and histopathological investigations were scheduled, and based on CT findings, further management was planned. Carcinoembryonic antigen levels were assessed in pre-operative and post-operative serum sample. Follow-up was done at regular intervals. CEA levels in subjects with different outcome were compared retrospectively. Results: The most common age group of subjects with colorectal malignancies was 51–60 years. Bleeding per rectum was the most common symptom and the most common sign was per rectal palpable mass. Laparoscopic surgery had less hospital stay, less blood loss, and lower rate of wound site infection. The pre-operative CEA levels were found to be matched; however, post-operative CEA levels were found to be significantly elevated in non-survivor subjects compared to those who survived. Conclusion: Patients with high post-operative CEA values should be closely followed up for relapse and dealt with more caution to reduce the mortality.